Task-shifting for point-of-care cervical cancer prevention in low- and middle-income countries: a case study from Uganda - Auma, Judith; Ndawula, Allan; Ackers-Johnson, James; Horder, Claire; Seekles, Maaike; Kaul, Veena; Ackers, Louise (Frontiers in Public Health, 2023)
Cervical cancer remains the leading cause of female cancer deaths in sub-Saharan Africa. This is despite cervical cancer being both preventable and curable if detected early and treated adequately. This paper reports on a series of action-research ‘cycles’ designed to progressively integrate a comprehensive, task-shifted, point-of-care, prevention program in a community-based public health facility in Uganda. The work has been undertaken through a UK-Ugandan Health Partnership coordinated by Knowledge for Change, a UK-registered Charity. The intervention demonstrates the effectiveness of task-shifting responsibility to Community Health Workers combined with the use of Geographic Information Systems to strategically guide health awareness-raising and the deployment of medical devices supporting respectful and sustainable point-of-care screen-and-treat services. The integration of this with public human immunodeficiency virus services demonstrates the ability to engage hard-to-reach ‘key populations’ at greatest risk of cervical cancer. The findings also demonstrate the impact of external influences including the Results Based Financing approach, adopted by many foreign Non-Governmental Organizations. The model presents opportunities for policy transfer to other areas of health promotion and prevention with important lessons for international Health partnership engagement. The paper concludes by outlining plans for a subsequent action-research cycle embracing and evaluating the potential of Artificial Intelligence to enhance service efficacy.